(untitled) (Research, Society and Development, 2020)
Seeking to understand the mechanisms of tolerance of melon plants under water deficit, this study aimed to evaluate the biochemical behavior of melon cultivars and the allocation of biomass under water deficit. Two experiments were conducted in a shaded environment in the experimental area of the State University of Bahia, Juazeiro / BA; the first was carried out in 2015 and the second in 2016. The experimental design was in randomized blocks, replicated three times, with subdivided plots; the plots consisted of four water application rates (50, 75, 100 and 125% of the crop evapotranspiration), the subplots of two melon cultivars ’Yellow’ and ’Piel de Sapo’. The sub-subplots were the sampling periods: 15; 30 and 45 days after transplantation. In the first experiment it was evaluated: total soluble sugars, reducing sugars, total proteins. In the second experiment, in addition to biochemical analyzes, the allocation of biomass of leaves, branches, roots, fruits and root / shoot ratio was evaluated. At the end of both experiments, root proline and aerial part were evaluated. Both cultivars showed similar biochemical behavior, except for the accumulation of proline obtained in the cultivar ’Piel de sapo’, which allowed greater biomass allocation to the fruit than the cultivar ’Amarelo’.